Advanced Technologies in the Quantification of Mitral Valve - Karvandi, Mersedeh (International Journal of Cardiovascular Practice, 2018)
The current study aimed at conducting an educational survey on the mitral valve using advanced technologies eSie ValveÂ® and Q-Lab in echocardiography machines and also those mitral valve geometrical parameter measurements that can be easily calculated with MATLAB software offline in a personal computer as an echocardiographic desk for further information and recommendation before mitral valve repairs or other treatments.